"Like Every Normal Person?!" The Paradoxical Effect of Aging With Schizophrenia. (May 2018) - Mushkin, Peli; Band-Winterstein, Tova; Avieli, Hila
Studies on aging with schizophrenia have focused mainly on the adversities of aging with mental illness. The present study, however, examined the subjective experience of well-being among individuals with schizophrenia. Taking a phenomenological reflective life-world approach, in-depth, semistructured interviews with 18 aging individuals with schizophrenia were thematically analyzed. Four main themes emerged: (a) "I love the pills . . . they are very helpful": A balanced course of the illness as a basis for well-being in old age; (b) "I'm going to have my own exhibition at the museum": Self-fulfillment as promoting well-being; (c) "It's just like a family here": Experiencing a sense of belonging; and (d) "I live like everyone else": Aging as an opportunity for normalization. Alongside hardship, the participants perceived old age as a "window of opportunity, " enabling the fulfillment of lifelong desires for a social life, acceptance, and a satisfying occupation. Implications regarding interventions with this unique population are discussed.